Educación y Tecnología, reflexiones en torno a una armonización - Romeo, Julia (Revista Chilena de Humanidades, 2015)
Professor Romeo Cardone is concerned with sorne of the most significant educational problems in these times of accelerated technological change. She points out the commitment of education to the formation of man, both as an individual and as a member of society. New concepts and procedures are proposed for the understanding of the human condition and of the corresponding educational tasks, while emphasizing the importan ce ofcurricula as the proper medium in the pedagogical process. Prof. Romeo Cardone conceives this process as a way towards self-fulfillment and, therefore, as an approximation to "peak experiences" in the terms expounded by A. H. Maslow.